Whaling on stage: a comparison of contemporary Japanese whale festivals - Rots, Aike P. (Religion, 2023)
Conservative Japanese politicians, academics, and journalists regularly state that whaling is an essential part of their national heritage, expressed in material culture, folk songs, ritual practices, and festivals. Japan has several whale festivals (kujira matsuri): playful events at which participants re-enact Edo-period (1600–1868) coastal whaling practices and perform whaling-related songs and dances. This article compares the festivals of Taiji (Wakayama), Kayoi (Yamaguchi), Shinkami-gotō (Nagasaki), and Ayukawa (Miyagi). It argues that these festivals not only have economic and social significance for the communities in question; they also support the notion of Japan as a traditional whaling nation. By organising and participating in these festivals, local priests, volunteers, and audiences enact this imagined whaling heritage, thus supporting the agenda of the present-day whaling industry. However, local actors have their own motivations and interests, and in fact the celebration of whaling heritage is not contingent upon the continuation of whaling today.